Efektivitas Pemanfaatan Weblog Sebagai Alternatif Media Pembelajaran di Masa Pandemi - Bayu Fitra Prisuna (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2022)
This study aims to determine the effectiveness of the use of weblogs in learning Islamic Cultural History at Madrasah Aliyah Negeri 2 Pontianak. This research approach is descriptive quantitative research with survey research type. The population in this study were all students of class XI at Madrasah Aliyah Negeri 2 Pontianak in 2020/2021 with a total of 260 people. Sampling used simple random sampling technique and resulted in a research sample of 157 people. Data collection techniques in this study used a questionnaire. Based on the results of research and discussion, it can be concluded that the effectiveness of the use of weblogs as learning media at Madrasah Aliyah Negeri 2 Pontianak tends to be effective in every dimension. This can be seen from the students' perception questionnaire on the effectiveness of the use of the website on the dimensions of the learning process showing 8% very good, 82% good, and 10% less; on the dimension of learning interest shows 25% very good, 57% good, and 18% less; while on the dimensions of learning outcomes 10% very good, 74% good, and 16% less.